Mimesis and alterity : a particular history of the senses - Taussig, Michael T. (New York : Routledge, 1993)
Contents: ##1. In some way or another one can protect oneself from evil spirits by portraying them ## 2. Physiognomic aspects of visual worlds ## 3. Spacing out ## 4. The golden bough: the magic of mimesis ## 5. The golden army: the organization of mimesis ## 6. With the wind of world history in our sails ## 7. Spirit of the mime, spirit of the gift ## 8. Mimetic worlds: invisible counterparts ## 9. The origin of the world ## 10. Alterity ## 11. The color of alterity ## 12. The search for the White Indian ## 13. America as woman: the magic of Western gear ## 14. The talking machine ## 15. His master's voice ## 16. Reflection ## 17. Sympathetic magic in a post-colonial age.
Includes bibliographical references (p. 283-290) and index.
boek